Calcule:
![{2}^{ - 1} {2}^{ - 1}](https://tex.z-dn.net/?f=+%7B2%7D%5E%7B+-+1%7D+)
![{2}^{ - 5} {2}^{ - 5}](https://tex.z-dn.net/?f=+%7B2%7D%5E%7B+-+5%7D+)
![{( - 2)}^{ - 2} {( - 2)}^{ - 2}](https://tex.z-dn.net/?f=+%7B%28+-+2%29%7D%5E%7B+-+2%7D+)
![{ - 2}^{ - 4} { - 2}^{ - 4}](https://tex.z-dn.net/?f=+%7B+-+2%7D%5E%7B+-+4%7D+)
![{ - ( - 4)}^{ - 3} { - ( - 4)}^{ - 3}](https://tex.z-dn.net/?f=+%7B+-+%28+-+4%29%7D%5E%7B+-+3%7D+)
![{10}^{ - 3} {10}^{ - 3}](https://tex.z-dn.net/?f=+%7B10%7D%5E%7B+-+3%7D+)
![- ( - 7) {}^{ - 2} - ( - 7) {}^{ - 2}](https://tex.z-dn.net/?f=+-+%28+-+7%29+%7B%7D%5E%7B+-+2%7D+)
Soluções para a tarefa
Respondido por
2
Calcule:
1 1
2⁻¹ = ------------ = ---------
2¹ 2
1 1 1
2⁻⁵ = -------------- = ----------------- = -----------
2⁵ 2x2x2x2x2 32
1 1 1
(-2)⁻² = ------------ = -------------- = ----------
(-2)² + 2x2 4
1 1 1
- 2⁻⁴ = - -------------- = - ------------ = - ----------
2⁴ 2x2x2x2 16
1 1 1 1
- (-4)⁻³ = - ----------- = - ---------- - (- ----------) = + ------------
(-4)³ - 4x4x4 - 64 64
1 1 1
10⁻³ = -------------- = ---------------- = --------------
10³ 10x10x10 1000
1 1 1 1
- (-7)⁻² = - -------------- = - ------------- = - ----------- = - ------
(-7)² + 7x7 + 49 49
1 1
2⁻¹ = ------------ = ---------
2¹ 2
1 1 1
2⁻⁵ = -------------- = ----------------- = -----------
2⁵ 2x2x2x2x2 32
1 1 1
(-2)⁻² = ------------ = -------------- = ----------
(-2)² + 2x2 4
1 1 1
- 2⁻⁴ = - -------------- = - ------------ = - ----------
2⁴ 2x2x2x2 16
1 1 1 1
- (-4)⁻³ = - ----------- = - ---------- - (- ----------) = + ------------
(-4)³ - 4x4x4 - 64 64
1 1 1
10⁻³ = -------------- = ---------------- = --------------
10³ 10x10x10 1000
1 1 1 1
- (-7)⁻² = - -------------- = - ------------- = - ----------- = - ------
(-7)² + 7x7 + 49 49
Respondido por
3
Boa noite!!!
2^-1 = 1/2
2^-5 = 1/2^5 = 1/2•1/2•1/2•1/2•1/2= 1/32
(-2)^-2 = (-1/2)^2= (-1/2)•(-1/2) = 1/4
-2^-4= (1/2)^4= 1/2•1/2•1/2•1/2= -1/16
-(-4)^-3= (-1/4)^3= (-1/4)•(-1/4)•(-1/4)= -(-1/64)= 1/64
10^-3= 1/10•1/10•1/10 = 1/1000
-(-7)^-2= (-1/7)^2= (-1/7)•(-1/7)= -(1/49)= - 1/49
Espero ter ajudado! :)
2^-1 = 1/2
2^-5 = 1/2^5 = 1/2•1/2•1/2•1/2•1/2= 1/32
(-2)^-2 = (-1/2)^2= (-1/2)•(-1/2) = 1/4
-2^-4= (1/2)^4= 1/2•1/2•1/2•1/2= -1/16
-(-4)^-3= (-1/4)^3= (-1/4)•(-1/4)•(-1/4)= -(-1/64)= 1/64
10^-3= 1/10•1/10•1/10 = 1/1000
-(-7)^-2= (-1/7)^2= (-1/7)•(-1/7)= -(1/49)= - 1/49
Espero ter ajudado! :)
Perguntas interessantes
Ed. Física,
11 meses atrás
Direito,
11 meses atrás
Matemática,
11 meses atrás
Física,
1 ano atrás
Direito,
1 ano atrás
Matemática,
1 ano atrás